Lessons Learned From the Effects of COVID-19 on the Training and Education Workflow of Radiology Residents—A Time for Reflection: Perspectives of Residency Program Directors and Residents in Canada. Issue 4 (November 2021) - Warnica, William; Moody, Alan; Probyn, Linda; Bartlett, Eric; Singh, Navneet; Pakkal, Mini
Purpose: The coronavirus disease 2019 (COVID-19) pandemic has led to widespread changes in all health care settings including academic radiology departments. The purpose of this survey-based study was to investigate the impact of COVID-19 on radiology resident training and education workflow in Canada in terms of the nature, scale, and heterogeneity of the changes, preparedness and adaptation, and perceptions of the present and future of radiology training. Methods: A 30-question web-based survey was sent to 17 radiology residency program directors across Canada. A separate 32-question survey was sent to 460 residents currently enrolled in a radiology residency in Canada. These surveys were open for 3 weeks. Results: We received responses from 16 program directors and 80 residents (response rates 94.1% and 17.4%, respectively). Most respondents agreed that objectives were being met for knowledge and interpretation but less so for case volumes and technical skills. Less time was allotted for on-site activities (eg, readouts) with more time for off-site activities (eg, videoconferencing). Daytime rotations were at least partly cancelled. Most respondents felt these changes were met with enthusiasm by both faculty and residents. However, there were perceived challenges including lack of training on virtual platforms for delivery of teaching and decreased staff–resident interaction, with short- and long-term anxiety reported. Conclusions: The coronavirus disease 2019 has dramatically changed radiology resident training in Canada, with increased virtual learning at the expense of cancelled rotations and the resultant reduction in case volumes and staff–resident interaction. Although adopted with enthusiasm, these changes present substantial challenges and anxiety regarding the future of radiology resident education.